Another alien bug in Europe: the first case of transcontinental introduction of the Asiatic burrower bug Macroscytus subaeneus (Dallas, 1851) (Hemiptera: Heteroptera: Cydnidae) to the U.K. through maritime transport - Lis, Jerzy A.; Whitehead, Paul F. (Zootaxa, 2019)
The Oriental burrower bug Macroscytus subaeneus (Dallas, 1851) (Hemiptera: Heteroptera: Cydnidae: Cydninae), presently known only from single localities in Flores (Indonesia), the Philippines and Thailand, is recorded from the United Kingdom (hereafter U.K.). A single female specimen was collected on the semi-rural edge of Bath city by a Starling (Sturnus vulgaris L.) and taken to its nest from which it was retrieved during 2015. The specimen is illustrated and its diagnostic characters are provided. We hypothesize that this specimen could have been imported with a shipping container from Thailand.